We are All Leaders: Introducing Self-Leadership Concepts Through the Lens of Improving Diversity in the Health Care Workforce - Raymond Lucas; Pooja Kothari; Clydell Adams; Latanya Jones; Valerie N. Williams; John Paul Sánchez (Association of American Medical Colleges, 2020)
Introduction Increasing faculty and leader diversity has been recommended as a way for health care organizations to achieve cultural competence in their patient care mission. Given the low numbers of underrepresented groups in medical school leadership positions, teaching diverse students and trainees the concept of leadership as influence may empower them to become more involved and bring diverse perspectives to their organizations. Methods This 70-minute workshop consisted of a short presentation, a self-assessment, small- and large-group discussions, and case studies to: (1) describe the importance of diversity in medical school leadership, (2) define leadership, (3) define self-leadership, and (4) assess one's own self-leadership skills. The workshop was implemented at three US medical schools to diverse medical students and residents between September and December of 2019. Pre- and postworkshop evaluations were analyzed. Results Greater than 95% of learners (n = 66) agreed that the workshop's learning objectives were met. Comments suggested participants appreciated learning about the lack of diversity among medical school leaders and the importance of cultivating their role in diversity in academic medicine. The case studies were highly rated and considered effective tools for learning. Discussion This submission defined an empowering notion of leadership as influence. It taught learners that we can all lead (by influence) if we can improve our own self-leadership skills and become involved and bring diverse perspectives to health care organizations. Future research may focus on longer-term follow-up of participants to reassess their self-leadership skills and describe their level of involvement in their organizations.